Selective Serotonin Reuptake Inhibitors and Risk of Gastrointesinal Bleeding In Dyspepsia: An Evidence-Based Case Report - Shatri, Hamzah; Zulkifly, Steven; Putranto, Rudi; Makmun, Dadang; Fauzi, Achmad; Maulahela, Hasan; Faisal, Edward; Irvianita, Vinandia; Ardani, Yanuar (The Indonesian Society for Digestive Endoscopy, 2023)
Aim: This evidence-based case report aims to provide the latest evidence about the risk of gastrointesinal (GI) bleeding in selective serotonin reuptake inhibitor (SSRI) users with dyspepsia.Method: The literature search was conducted in four major electronic databases (PubMed, Cochrane, Scopus, ProQuest). The selected articles were sorted through screening abstract based on the inclusion and exclusion criteria. Critical appraisal was performed by using validated critical appraisal tool.Results: Of 247 records from extensive literature searching, three eligible studies (one randomized clinical trial and two cohort studies) were obtained to answer the clinical question. All studies showed SSRIs did not increase the risk of GI bleeding in patients with functional dyspepsia and peptic ulcer. However, the adverse event of SSRIs might be under-reported.Conclusion: According to the evidence, the risk of GI bleeding in SSRIs users with dyspepsia is still unclear. Larger size of sample of controlled trial study is recommended to be conducted to calculate the precise risk of GI bleeding in SSRI users with dyspepsia.